Dual Ascent Algorithm-Based Improved Droop Control for Efficient Operation of AC Microgrid - Jiang, Yajie; Yang, Yun (Frontiers in Electronics, 2022)
In this work, distribution loss of island three-phase AC microgrid, including both wire loss and converter loss, is modeled as a quadratic function of current distribution coefficient, that is, a concave function with equality and inequality constraints. On the basis of concave optimization principle, the optimal current distribution coefficient of distributed energy unit (DEU) is calculated online by double ascent optimization method (DAOM) to minimize the distribution loss. It is proofed that the concave function with multi-variables can be optimized by DAOM. Using the average reactive power distribution scheme, the optimal active power distribution coefficient with the minimum distribution loss of AC microgrid can be obtained in real time. Besides, given the high R/X ratio in low-distance AC microgrid, the active power-frequency (P-ω) droop control and reactive power-voltage amplitude (Q-E) droop control aren’t suitable for power distribution among DEUs. Thus, an advanced strategy, composed of active power-voltage amplitude (P-E) droop control and reactive power-frequency (Q-ω) droop control are proposed to dispatch the output active powers and reactive powers of DEUs. Simulation examples are provided to verify the convexity of the proposed model and the effectiveness of the control strategy.